Radionuclide transport in the boreal landscape : Uranium, thorium and other metals in forests, wetlands and streams - Lidman, Fredrik (Umeå universitet, Institutionen för ekologi, miljö och geovetenskap, 2013)
The boreal landscape is complex mosaic of vast forests, lakes and wetlands. Through the landscape flows a fine network of streams and rivers, carrying dissolved and suspended material from atmospheric deposition and weathering of soils and bedrock to downstream recipients. This thesis investigates the transport of U, Th and other metals in the boreal landscape by comparing a set of catchments with contrasting characteristics, ranging from 0.12-68 km2 in area. Using uranium (234U/238U) and oxygen isotopes (δ18O) it was demonstrated that catchment size has a strong impact on the hydrological pathways and on the mobilisation of uranium. Both tracers also displayed a consistent shift towards more superficial sources and more superficial flow pathways when going from winter baseflow conditions to the spring flood. Large spatiotemporal variability was observed with U fluxes ranging from 1.7 -30 g km-2 a-1. Using a wide set of hydrochemical parameters and landscape characteristics it was demonstrated that wetlands play a decisive role for the biogeochemical cycling of many metals. Comparing normalised fluxes of 13 different elements (Al, Ba, Ca, Cr, Cu, La, Mg, Na, Ni, Si, Sr, U and Y) 73% of the spatial variance could be explained based on the wetland coverage and the affinity for organic matter, the latter of which was quantified using thermodynamic modelling. Hence, it was possible to link the large-scale transport patterns of a wide range of metals to fundamental biogeochemical properties. When restraining the analysis to the smaller streams (<10 km2), the explanatory power increased to 88%. For elements such as Na and Si with low affinity for organic matter the decrease in wetland-dominated catchments corresponded closely to the area of mineral soils that had been replaced by peat, indicating that reduced weathering was the main cause of the decrease. For organophilic metals the decrease in wetland-dominated catchments was even greater, suggesting that there also was an accumulation of these metals in the peat. This was confirmed by investigating the distribution of radionuclides in local mire, which revealed considerable accumulation of uranium and thorium along the edges of the mire. Based on the inventories of uranium and thorium and their distribution in the peat it was concluded that the mire historically had been a sink for these metals and that it most likely will continue to be so for a long time to come. All and all, wetlands were estimated to decrease the fluxes of metals from the boreal forests to downstream lakes and oceans by 20-40%, depending on how strongly they bind to organic matter.